Comparison of multiple synthetic chondroinductive factors in pellet culture against a TGF-β positive control - Boushra Ajeeb; Michael Detamore (Osteoarthritis and Cartilage Open, 2023)
Despite the advances in surgical and cell therapy regenerative techniques for cartilage repair, the challenge is to overcome an inferior fibrocartilage repair tissue. In vitro, TGF-β1 and TGF-β3 are the primary growth factors employed to induce chondrogenic differentiation. However, the clinical application of native proteins may present challenges regarding stability, cost, or reproducibility. Therefore, there remains an unmet clinical need for the identification of small chondroinductive synthetic molecules. From the literature, two peptides—CM10 and CK2.1—appear to be promising candidates; however, they have not been directly compared to TGF-β with human bone marrow-derived stem cells (hBMSCs). Similarly, two promising compounds—kartogenin and SM04690—have been reported in the literature to exhibit chondroinductive potential in vivo and in vitro; however, kartogenin was not directly compared against TGF-β. In the current study, we evaluated the chondroinductive potential of CM10, CK2.1, kartogenin, and SM04690, and directly compared them to each other and to a TGF-β3 positive control. Following 21 days of culture, none of the evaluated chondrogenic factors, either individually or even in combinations of two, resulted in a higher gene expression of chondrogenic markers as compared to TGF-β3. Additionally, no collagen II gene expression was detected except in the TGF-β3 positive control group. Given that the evaluated factors have confirmed efficacy in the literature, but not in the current study with a positive control, there may be value in the future identification of new chondroinductive factors that are less situation-dependent, with rigorous evaluations of their effect on chondrogenesis using positive controls.